Paciente masculino de 69 años de edad con cáncer de pulmón - Bravo Almache, Julisa Valeria (2020)
The present clinical case focuses on the health and lifestyle of the male patient of 69 years of age, constant smoking habit the patient showed symptoms similar to said pathology were tested to arrive at a definitive diagnosis resulting in lung cancer, identifying the risk factor in this clinical case as a cause of this pathology due to excessive tobacco use the patient should receive the palliative treatment provided by the health team. The patient has oxygen support with venturi mask with a saturation of 99% and enteral feeding by nasogastric tube. The process of this clinical case focuses on recognizing lung cancer as one of the fundamental pathologies for public health because of its high rate of morbidity and mortality worldwide, it is important that society is aware of the risk of this pathology and the consequences it would have on the life of the person. The primary objective of this study is to determine respiratory therapy actions in the lung cancer patient for the purpose of providing respiratory support during disease development. This respiratory pathology such as lung cancer is considered to have resting dyspnoea, cachexia, afebril, dysphagia. Generally presenting poor respiratory mechanics so oxygen support is essential in these patients to keep the airways permeable.